Worldviews overarching concept, discrete body of knowledge or paradigmatic tool? - Flanagan, Ruth (2020)
The term ‘worldviews’ is employed across disciplinary boundaries, yet with no agreed definition it may actually obscure rather than clarify meaning. The use of the term has grown in frequency, particularly in Religious Education (RE) in England, since the Commission on RE’s final report (2018), which recommended changing the name of RE to ‘Religion and worldviews’. Response to the report has been mixed. Some fear that an introduction of worldviews may lead to a dilution of RE and overburden an already overstretched teaching profession; others welcome a meaningful study of non-religious worldviews which they view as more pertinent in the current growth of ‘nones’ (Nones’ term used for those who adhere to ‘no faith’, see Woodhead (J Br Acad 4:245-261, 2016)) in England. Teaching worldviews raises questions of selection: are all worldviews equally appropriate for pupils to study and consistent with the aims of education? For example, is it appropriate for a 6 year old to study Hedonism or National Socialism? This paper problematizes the binary nature of the debate and interrogates the usage of the term 'worldviews'. Focusing on ‘institutional worldviews’ is questionable as the role of master narratives, embedded in these, lose currency. The ‘disintegration of master narratives’, (Riessman in Narrative Methods for the Human Sciences. SAGE Publications, Thousand Oaks, 2008, p. 17), has led to a rise in individuals creating their personal embodied worldviews, albeit subconsciously. Rather than consider worldviews as a discrete body of knowledge that imposes on an already overburdened curriculum, I propose that employing worldviews as an overarching concept, providing a type of paradigmatic analysis for RE, may lead to a greater and more profound understanding of religion(s).
Keywords: Religious Education; Teachers; Worldviews